Jouer dans un monde informatisé : l’imaginaire informatique dans les jeux de rôle cyberpunk - Isabelle Périer (ReS Futurae)
This paper aims to study how computer imaginary evolved from the end of the eighties until our days. To achieve this, we’ll scrutinize two famous cyberpunk pen and paper role playing game’s fictional worlds : Cyberpunk and Shadowrun. After a short description of those fictional worlds, we’ll study how computer imaginary evolved through the many editions of those RPG to emphasize two main ideas : the revolution of wireless hardware and the paradoxical democratization and complexity of computers. After which, we’ll show the permanence and consistency of some notions and representations : how computers are linked to capitalism and the idea of power or violence, and how computers are often related to the idea of magic.